2022
DOI: 10.3390/su14169893
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the Unprotected Consumer Data in Internet of Things: Current Scenario of Data Governance in Malaysia

Abstract: With the increasing number of smart devices and connections in Internet of Things (IoT) comes risks—specifically involving consumer data protection. In this respect, this exploratory research examines the current issues of IoT and personal data protection in Malaysia that includes: regulatory frameworks and data governance; issues and gaps; and key challenges in implementation. Results from this mixed-methods research indicates that a majority of consumers expressed concern about personal data risks due to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
2
1
Order By: Relevance
“…These results support the findings of other studies that found that found that personal financial education is crucial in reducing personal bankruptcy as well consumer credit delinquency rates (Gupta andPrusty, 2023, Baulkaran, 2022). However, our study's findings significantly differ from those of Cheryl and Ng (2022) who's study on protecting the unprotected consumer data in the internet of things (IoT) concluded that majority of consumers expressed concern about their personal data risks due to the IoT usage. This finding is also overwhelmingly supported in the literature (Xiao and Bialowolski, 2023, Xiao, 2016, Xiao et al, 2015, Xiao et al, 2014.…”
Section: Empirical Results Analysis and Discussioncontrasting
confidence: 99%
“…These results support the findings of other studies that found that found that personal financial education is crucial in reducing personal bankruptcy as well consumer credit delinquency rates (Gupta andPrusty, 2023, Baulkaran, 2022). However, our study's findings significantly differ from those of Cheryl and Ng (2022) who's study on protecting the unprotected consumer data in the internet of things (IoT) concluded that majority of consumers expressed concern about their personal data risks due to the IoT usage. This finding is also overwhelmingly supported in the literature (Xiao and Bialowolski, 2023, Xiao, 2016, Xiao et al, 2015, Xiao et al, 2014.…”
Section: Empirical Results Analysis and Discussioncontrasting
confidence: 99%
“…The implementation of digital identity programs without thorough consideration of cybersecurity and privacy increases the risk of cyberattacks and security vulnerabilities [195]. SDG 17: Partnerships for the goals Global Data Sharing Security Collaborative efforts among nations require secure data sharing to achieve the SDGs, while addressing concerns about data privacy, ownership, and misuse [196]. Empirical evidence shows that the need for secure and integrity-preserved data sharing has become increasingly important in the emerging era of changed demands on healthcare and increased awareness of the potential of data [197].…”
Section: Sdg Key Challenge Cybersecurity Concernmentioning
confidence: 99%
“…To address these challenges, legal frameworks and regulations play a critical role. Governments are tasked with developing and implementing laws that define the scope of surveillance and data collection, as well as the rights and protections afforded to individuals (Cheryl and Ng, 2022). Striking the right balance requires clear and well-defined legal parameters that restrict surveillance to what is strictly necessary and proportionate for security purposes.…”
Section: Security Privacy and The Complex Landscapementioning
confidence: 99%